The Insistence of Art : Aesthetic Philosophy after Early Modernity - Kottman, Paul A., 1970- (Book collections on Project MUSE., 2017)
"Philosophers working on aesthetics have paid considerable attention to art and artists of the early modern period. Yet early modern artistic practices scarcely figure in recent work on the emergence of aesthetics as a branch of philosophy over the course the eighteenth century. This book addresses that gap, elaborating the extent to which artworks and practices of the fifteenth through the eighteenth centuries were accompanied by an immense range of discussions about the arts and their relation to one another"--